Pengembangan media pembelajaran interaktif berbantuan articulate storyline pada materi kecepatan dan debit untuk peserta didik kelas V sekolah dasar - Joko Susilo; Riyadi Riyadi; Hadiyah Hadiyah (Universitas Sebelas Maret, 2023)
This study aims to determine the process and results of developing learning media for speed and discharge materials assisted by Articulate Storyline that are valid and practical. This research uses research and development methods. This development research uses ten steps of research and development from Borg and Gall which have been modified into three stages, namely preliminary studies, model development, and model tests. This research is limited only to the second stage, namely model development. Data sources in this study include teachers and students of grade V SD Negeri 16 Surakarta, media experts and material experts. The result of this research is the development of valid and practical learning media obtained through two stages, namely the preliminary study stage, including problem analysis, student analysis, competency analysis, flowchart design, media production, and media validation by media experts and material experts then improvements are made; and Media development stage by conducting limited trials. The resulting learning media was declared valid based on the assessment of media experts with a result of 87.5% and the assessment of material experts with a result of 87%. The resulting learning media was also declared practical based on the assessment of students with a result of 92.3%.